Customer Switching-Behavior Case Ojek Offline To Ride Hailing Influenced By Price, Service Quality, And Customer Experience - Muhammad Khoir Rozin (Institute of Computer Science (IOCS), 2022)
Currently, Indonesian always use transportation modes to carry out their daily activities. Developments that occur in the transportation sector combined technology and conventional concepts which were previously ojek offline into ojek online (ride-hailing). This study aims to determine the effect of price, service quality, and customer experience on customer switching-behavior in the case of ojek offline to ojek online. Sampling used is convenience sampling by distributing questionnaires to people who had used ojek offline and switched to ojek online, then the results of the questionnaire were processed using PLS-SEM analysis. This study measures the effect of price, service quality, and customer experience on customer switching-behavior by using a Likert scale. The sample in this study used convenience sampling with totals 201 respondents consisting of customers who have used ojek offline and then have switched to ojek online. This study obtained the results that price, service quality, and customer experience have a simultaneous effect on customer switching-behavior by 77.2% on customer switching-behavior. The results of the dimensions to customer experience affect 100% with accessibility, customer recognition, personalization, helpfulness, and value for time which have a significant influence on customer experience. However, the dimensions of competence and promise fulfillment do not significantly affect the customer experience.